Modeling broken rotor bar faults in induction motors: a combined SSFR and FEM approach - Mabrek, Abdelhakim; Elyazid, Zaidi; Selmoune, Bachir; Hemsas, Kamel Eddine (Institute of Advanced Engineering and Science, 2025)
The fault of broken rotor bar (BRB) yields to high levels of stress in induction motor drive (IM) and being a common fault. This paper proposes a novel hybrid approach combining standstill frequency response (SSFR) testing and finite element method (FEM) modeling to improve fault diagnosis accuracy. The findings were verified experimentally using a 7.5 kW three-phase IM by SSFR approach under various failure scenarios. Reliability of SSFR method is confirmed by the use of FEM, flux 2D magnetic analysis software is employed on the same IM using in SSFR to determine the magnetic field under different fault and load conditions. The work is finished by current harmonics analyses and the outcomes of the BRB model demonstrate that the combined method enhances fault detectability, particularly for incipient and partial bar breakages, reducing false alarms compared to conventional techniques.